Iridescence in Meat and Fish - Swatland H. J. (Current Perspectives in Agriculture and Food Science Vol. 7, 2024)
The iridescence of meat and fish was investigated by fiber optic and microscope spectrophotometry. The metallic colors of iridescence were thought to originate from multilayer interference along myofibers. When muscles are not iridescent these multiple reflectances contribute to light scattering and meat paleness.